A Novel Method Based on the Post Correspondance Problem for Designing Cryptosystems - Ho, Ngoc Vinh; Nguyen, Dinh Han (Old Journal, 2017)
Cryptography is an integral part of computer science. Nowadays, cryptosystems are one of the most important applications of cryptography. In communication area, cryptosystems can be used to establish cryptographic protocols and algorithms for transmitting data securely via an unsafe enviroment such as Internet. Recent advances in cryptoanalysis and computing have exhibited a lot of weeknesses of existing cryptosystems. Therefore, it is most urgent that cryptography establishes new powerful cryptosystems. In this paper, we present a novel method to design cryptosystems as the standard approach to protect data. The obtained cryptosystems contain a trapdoor which can be reduced to an undecidable problem, namely the POST correspondance problem.